New Insights into the Catalytic Activity and Reusability of Water‐Soluble Silver Nanoparticles. Issue 29 (11th August 2021) - Monti, Gustavo A.; Correa, N. Mariano; Falcone, R. Darío; Silbestri, Gustavo F.; Moyano, Fernando
Abstract: Silver nanoparticles (AgNPs) ‐stabilized by different sulfonated imidazolium salts (Lx )‐ have been synthesized as potential recyclable and reusable catalysts for the reduction of nitroaromatic compounds in water. An exhaustive study of the catalytic activity is presented and kinetic data are explained in terms of the Langmuir–Hinshelwood model. The kinetic parameters and the performance of AgNP as catalysts were determined. The results reveal that catalysis is a superficial process and the reaction rate depends on the type of AgNP:Lx used as catalyst, with the imidazolium salts having the effects on the catalytic activity. The physicochemical and structural characteristics of AgNPs are factors that influence the catalytic efficiency. The fact that these catalysts are recycled, in some cases for more than 6 cycles, opens a way for their recovery and reuse of AgNPs. Finally, a comparative study with gold nanoparticles (AuNP) stabilized by the same salts has been realized. Abstract : New water‐soluble catalysts with excellent activity for the reduction of 1, 4‐dinitrobenzene at room temperature in water